Cavity dumping by the second harmonic generation - Gorbatsevich, Alexander S.; Navitskaya, Roza I.; Stashkevich, Ihar V. (Journal of the Belarusian State University. Physics, 2017)
In this paper we propose a method of cavity dumping by the second harmonic generation. Theoretical modeling of laser operation in this mode has been performed, the main characteristics of the output pulse have been calculated, and the effect exerted by the characteristics of the setup elements on the pulse duration and intensity has been examined. It is shown that a minimum length of the output pulse is equal to the time required for double-passing the cavity. The peak intensity of the pulse nonlinearly decreases with the increased ratio of inactive loss within the cavity. This affords an opportunity to generate stable duration nanosecond pulses of the second harmonic, the peak intensity being increased with the pump power and decreased with increasing operation time of the electrooptic crystal. The pulse duration can be controlled by changing the polarizer transmittance, and also the electrooptic crystal response time that at best is about 1 ns. The method is implemented experimentally.